Exploring The Multifaceted Dimensions of Manhood in Biblical Narratives Using King David’s Life - Dlodlo, Nozipho Princess S.; Nkatini, Hundzukani P. Khosa (KAMASEAN: Jurnal Teologi Kristen, 2023)
The episode from the life of King David in this article served as a case study as we tried to explore the link between men and violence in contemporary society. In restating the hypothesis, we posit that men in our daily society sometimes reference Christian Biblical characters in their process of understanding their masculinity construction process and masculine traits. If this is the case, we have found that Christian men continue to hide under the shadow of emulating Biblical male characters in their navigation of this transition process and sustaining violent masculinity traits. We took cognizance of how some men move seamlessly between culture and faith as and when the transition process favors them. We used the narrative analysis method to examine this research. This article is premised on other factors, such as David being known in the community as the boy who killed a giant, as this makes it quick for people in the community and the church to remember him. This article explored the question of whether there were no better Biblical models for men to follow that could offer a wholesome insight into the construction of masculinity. While David was a man after God’s heart, he exuded violence, and his household continued to use power to abuse those within the household.